Correction: Surface modification of intraocular lenses with hyaluronic acid and lysozyme for the prevention of endophthalmitis and posterior capsule opacification. Issue 12 (7th March 2022) - Wang, Bailiang; Lin, Quankui; Jin, Tingwei; Shen, Chenghui; Tang, Junmei; Han, Yuemei; Chen, Hao
Abstract : Correction for 'Surface modification of intraocular lenses with hyaluronic acid and lysozyme for the prevention of endophthalmitis and posterior capsule opacification' by Bailiang Wang et al., RSC Adv., 2015, 5, 3597–3604, DOI: ; 10.1039/c4ra13499k .